Structure, evolution and expression of zebrafish cartilage oligomeric matrix protein (COMP, TSP5). CRISPR-Cas mutants show a dominant phenotype in myosepta - Forte-Gomez, Helena Fabiana; Gioia, Roberta; Tonelli, Francesca; Kobbe, Birgit; Koch, Peter; Bloch, Wilhelm; Paulsson, Mats; Zaucke, Frank; Forlino, Antonella; Wagener, Raimund (Frontiers in Endocrinology, 2022)
COMP (Cartilage Oligomeric Matrix Protein), also named thrombospondin-5, is a member of the thrombospondin family of extracellular matrix proteins. It is of clinical relevance, as in humans mutations in COMP lead to chondrodysplasias. The gene encoding zebrafish Comp is located on chromosome 11 in synteny with its mammalian orthologs. Zebrafish Comp has a domain structure identical to that of tetrapod COMP and shares 74% sequence similarity with murine COMP. Zebrafish comp is expressed from 5 hour post fertilization (hpf) on, while the protein is first detectable in somites of 11 hpf embryos. During development and in adults comp is strongly expressed in myosepta, craniofacial tendon and ligaments, around ribs and vertebra, but not in its name giving tissue cartilage. As in mammals, zebrafish Comp forms pentamers. It is easily extracted from 5 day post fertilization (dpf) whole zebrafish. The lack of Comp expression in zebrafish cartilage implies that its cartilage function evolved recently in tetrapods. The expression in tendon and myosepta may indicate a more fundamental function, as in evolutionary distant Drosophila muscle-specific adhesion to tendon cells requires thrombospondin. A sequence encoding a calcium binding motif within the first TSP type-3 repeat of zebrafish Comp was targeted by CRISPR-Cas. The heterozygous and homozygous mutant Comp zebrafish displayed a patchy irregular Comp staining in 3 dpf myosepta, indicating a dominant phenotype. Electron microscopy revealed that the endoplasmic reticulum of myosepta fibroblasts is not affected in homozygous fish. The disorganized extracellular matrix may indicate that this mutation rather interferes with extracellular matrix assembly, similar to what is seen in a subgroup of chondrodysplasia patients. The early expression and easy detection of mutant Comp in zebrafish points to the potential of using the zebrafish model for large scale screening of small molecules that can improve secretion or function of disease-associated COMP mutants.